Dielectric laser accelerators: photonic control, electron compression, and quantum sensing - Zhao, Zhexin; Black, Dylan S.; Sun, Xiao Qi; Hughes, Tyler W.; Leedle, Kenneth J.; Tan, Si; Joel England, R.; Solgaard, Olav; Byer, Robert L.; Fan, Shanhui; Hommelhoff, Peter (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We discuss how photonic control addresses key challenges of dielectric laser accelerators (DLAs) and propose applications using DLAs, i.e., electron pulse compression and quantum sensing of two-level systems.
CRIS-Team Scopus Importer:2024-10-04